2020
DOI: 10.1039/d0ra06239a
|View full text |Cite
|
Sign up to set email alerts
|

When biomolecules meet 2-hydrazinopyrazine: from theory through experiment to molecular levels using a wide spectrum of techniques

Abstract: Structure, ionic forms, hydrophilic and non-cytotoxic character of 2-hydrazinopyrazine with stronger affinity to BSA than DNA were proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…It can be seen that both calculated values are negative, which indicates the hydrophilic character of 2Cl3HP. In addition, the values are all above that of 2HP [1]. A comparison analysis of logP values determined previously for 2HP (−0.468) and those found in the safety data sheet for 2Cl3HP (−0.935) suggested the introduction of a Cl atom instead of an H atom to the third position of the 2HP ring causes a change in logP value.…”
Section: Frontier Molecular Orbitals (Fmos) Considerations and Uv-vis...mentioning
confidence: 59%
See 4 more Smart Citations
“…It can be seen that both calculated values are negative, which indicates the hydrophilic character of 2Cl3HP. In addition, the values are all above that of 2HP [1]. A comparison analysis of logP values determined previously for 2HP (−0.468) and those found in the safety data sheet for 2Cl3HP (−0.935) suggested the introduction of a Cl atom instead of an H atom to the third position of the 2HP ring causes a change in logP value.…”
Section: Frontier Molecular Orbitals (Fmos) Considerations and Uv-vis...mentioning
confidence: 59%
“…The dependence of [DNA]/(εa − εf) as a function of [DNA] was plotted to determine the actual binding constant value describing the specific type of interactions in the studied system (Figure 8B). Interestingly, it is also possible to perform a comparative analysis of the two typical low-molecular binders: 2HP [1] and 2Cl3HP. Based on their values of the binding constant, it can be concluded that 2Cl3HP interacts with DNA almost 1.65-fold stronger compared to 2HP.…”
Section: Cl3hp Affinity To Ct-dnamentioning
confidence: 99%
See 3 more Smart Citations